Pemikiran Tasawuf Anregurutta H. Abdurahman Ambo Dalle - Mursalim, Mursalim (FENOMENA, 2015)
This research wants to know proprietary tasawuf thinking by Anregurtta H. Abdurrahman Ambo Dalle (called Ambo Dalle) in his book in Bugiss lingual version âal Qawl al shadiq li Ma â rifat al Khaliq / ada tongeng tongengnge ri annessana pappejeppue ri puang pancajieâ. Thus, this research is bibliographical observational type (library research) one that gets character descriptive analysis. Anregurutta Abdurrahman Ambo Dalle is constitute ulamas figure that combine among knowledge syariat and tasawufs knowledge. Harmony who did by Anregurutta among knowledge syariat with reality knowledge is an effort for unbent tarekats concept or flow (tasawuf) one that amends, notably on Bugiss society who restrains from al Quran and hadits. That thing is looked while Anregurutta combine among bodily religious service and spritual religious service, one that religious service comes into the world is territorial temporary carnal job religious service, spritual is territorial heart job which is as recitation (remember) to God and that is core than religious service in Islamic. Such too its criticism to tasawufs teaching with concept ittihad and hulul,Â  which is a concept that teaches one to declare for self a slave until to its The Infinite upon remembers (recitation) and at that moment as one with God, therefore expression âØ§ÙØ¹Ø§Ø¨Ø¯ ÙØ§ÙÙØ¹Ø¨ÙØ¯ ÙØ§ØØ¯ â while Anregurutta Ambo Dalle is â Ø§ÙØ¹Ø§Ø¨Ø¯ ÙØ§ØØ¯ ÙØ§ÙÙØ¹Ø¨ÙØ¯ ÙØ§ØØ¯ â